The policy of free healthcare for children under the age of 6 years in Vietnam: assessment of the uptake for children hospitalised with acute diarrhoea in Ho Chi Minh City. Issue 12 (18th October 2013) - Shieh, Mae; Thompson, Corinne; Phan Vu Tra, My; Thi Thuy Linh, Van; Tediosi, Fabrizio; Merson, Laura; Farrar, Jeremy J.; Manh Tuan, Ha; Lu Viet, Ho; Thi Ngoc Tuyet, Pham; Baker, Stephen
Abstract Objective To assess the proportion of, and reasons for, households not utilising the policy of free healthcare for children under 6 years of age (FCCU6) for hospitalisation with diarrhoea, and assess the risk of catastrophic expenditure for households that forgo FCCU6 and pay out of pocket. Methods Invoices detailing insurance information and charges incurred from 472 hospitalised diarrhoeal cases in one paediatric hospital in Ho Chi Minh City were retrieved. Hospital charges and the utilisation of elective services were analysed for patients utilising and not utilising FCCU6. Associations between socio‐economic factors with non‐utilisation of FCCU6 were evaluated. Results Overall, 29% of patients were FCCU6 non‐users. The FCCU6 non‐users paid a median hospital charge of $29.13 (interquartile range, IQR: $18.57–46.24), consuming no more than 1.4% of a medium‐income household's annual income. Seventy per cent of low‐income FCCU6 non‐users utilised less‐expensive elective services, whereas only 43% of medium income patients and 21% of high‐income patients did (P = 0.036). Patients from larger households and those with a parent working in government were more likely to use FCCU6. Conclusions The rate of FCCU6 non‐usage in this study population was 29%. A significant proportion of those that did not use FCCU6 was from lower income households and may perceive a justifiable cost–benefit ratio when forgoing FCCU6. Although a single diarrhoeal hospitalisation is unlikely to induce a catastrophic expenditure, FCCU6 non‐usage may disproportionately increase the risk of catastrophic expenditure for lower income households over multiple illnesses.